PENANGANAN PERKARA TINDAK PIDANA PENADAHAN DI PENGADILAN NEGERI SEMARANG - Sugiyono Sugiyono; Umar Ma’ruf (Jurnal Hukum Khaira Ummah, 2018)
Evil is an eternal problem, as long as humans inhabit this earth. One of the crimes that appear in the community of criminal acts of offense . The issues raised in this research are (1) How is the handling of criminal case of offense in Semarang District Court (2) How Judge Consideration Criminal in Case of offense Criminal Decision Number 754 / Pid / B / 2013 / PN Smg. The method used in this research is sociological juridical, The sociological juridical method is an approach that aims to describe a fact that is in the field based on legal principles and legislation. The research finding that (1) case handling Number: 754 / Pid / B / 2013 / PN Smg is correct based on examination process of witness testimony, defendant's statement and evidence proven in court (2) Judge Consideration of Criminal in Case of offense Criminal has been in accordance with Article 183 Criminal Procedure Code on the basis of decision and Article 184 Criminal Procedure Code as well as reinforced by Judge's conviction. Keywords : Criminal offense, Article 480